The Concept of Learning Objectives, Educators, and Learners in the Perspective of ‘Athiyah Al-Abrasyi - Putri Shofi Amalia; Moch. Farich Alfani (Mentari : Journal of Islamic Primary School, 2025)
This study is motivated by the condition of Islamic education, which is often limited to educational practice and has not yet reached the fulfillment of a clear spiritual–religious (ruḥāniyyah Islāmiyyah) connectedness. In addition, the slow growth and development of Islamic education did not only occur during the medieval period but continues to persist in the present era. In general, his thoughts on Islamic education were strongly influenced by the ideas of Ibn Sina, Ibn Miskawaih, Imam al-Ghazali, and Ibn Khaldun. Meanwhile, ‘Athiyah Al-Abrasyi was an Egyptian scholar, educational figure, Islamic scholar, and professor. This research employs a literature study method with a systematic qualitative approach using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. Data were collected from classical Islamic scholarly texts (kutub al-turāth) of early Muslim scholars as well as from research articles published between 2015 and 2023 in national and reputable international journals. The findings of this study conclude that: (1) the concept of learning objectives proposed by ‘Athiyah Al-Abrasyi primarily focuses on the development of the soul and moral character; however, other objectives remain essential and should not be neglected. These supporting objectives include maintaining a balance between worldly and hereafter interests, considering practical benefits, pursuing knowledge for its own sake, and emphasizing vocational and technical education as a means of earning a livelihood; (2) the concept of educators according to ‘Athiyah Al-Abrasyi is not limited to the enhancement of professional competence. Educators must also possess ideal moral qualities so that they are respected, obeyed, and able to serve as exemplary role models in both conduct and behavior; and (3) the concept of learners according to ‘Athiyah Al-Abrasyi emphasizes that learners possess both rights and obligations, which serve as guiding principles for Islamic education.